Faktor Yang Mempengaruhi Tingkat Pengangguran Di Beberapa Negara Asean - Faris Dzulfiqar (Economics and Digital Business Review, 2024)
This research aims to determine the influence of population, inflation Gross Domestic Product and Foreign Direct Investment on unemployment in ASEAN countries. This research is quantitative research using panel data regression methods with econometric models. The results of the simultaneous significant test (F test) show that in 2017-2022 the variables Population Growth (PP), Gross Domestic Product (GDP), Inflation (INF), and Foreign Direct Investment (FDI) simultaneously influenced the poverty level in 2017-2022. 2022. The results of the t test show that the variables Population Growth (PP) and Gross Domestic Product (GDP) have a significant effect on unemployment in several ASEAN countries in 2017-2022. Meanwhile, the variables Inflation (INF) and Foreign Direct Investment (FDI) do not have a significant effect on unemployment in several ASEAN countries in 2017-2022.